1997
DOI: 10.1016/s0006-3495(97)78820-9
|View full text |Cite
|
Sign up to set email alerts
|

Single-particle tracking: the distribution of diffusion coefficients

Abstract: In single-particle tracking experiments, the diffusion coefficient D may be measured from the trajectory of an individual particle in the cell membrane. The statistical distribution of single-trajectory diffusion coefficients is examined by Monte Carlo calculations. The width of this distribution may be useful as a measure of the heterogeneity of the membrane and as a test of models of hindered diffusion in the membrane. For some models, the distribution of the short-range diffusion coefficient is much narrowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
557
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(586 citation statements)
references
References 32 publications
28
557
0
1
Order By: Relevance
“…The broad diffusivity distribution of our model is in agreement with several experimental reports [17]. In addition, it accounts for the presence of heterogeneity in interaction products (i.e., formation of clusters with a varying number of molecules and thus different diffusivities) as well as in interacting partners (i.e., interactions with a pool of chemically different species with different diffusivity) that can be found in the cellular environment.…”
Section: Introductionsupporting
confidence: 89%
“…The broad diffusivity distribution of our model is in agreement with several experimental reports [17]. In addition, it accounts for the presence of heterogeneity in interaction products (i.e., formation of clusters with a varying number of molecules and thus different diffusivities) as well as in interacting partners (i.e., interactions with a pool of chemically different species with different diffusivity) that can be found in the cellular environment.…”
Section: Introductionsupporting
confidence: 89%
“…Wade et al reported that the diffusion constants of molecules in the cell membrane follow a lognormal distribution. 22,23 In our study, the distribution of diffusion constants was fitted with a lognormal distribution and the mean diffusion constant was 3.2 ± 0.4 nm 2 /s. This is the first report of the observation of molecular dynamics on a living cell surface using HS-AFM.…”
Section: Dynamic Molecular Movement On Living Cellsmentioning
confidence: 83%
“…The VeGe fluorescence mass center was tracked with MIA using a shape recognition algorithm. Values of the mean square displacement (MSD) were calculated from the resulting trajectories with Matlab (The Mathworks S.A.S., Sèvres, France) applying the relation MSD (ndt) (Saxton, 1997), where x i and y i are the coordinates of an object on frame i, N is the total number of steps in the trajectory, dt is the time interval between two successive frames, and ndt is the time interval over which displacement is averaged. The diffusion coefficients were calculated by computing the MSD curves.…”
Section: Introductionmentioning
confidence: 99%
“…The trajectories were typically composed of 100 points. The MSD was considered over the first 30 time intervals to avoid large statistical fluctuations (Saxton, 1997). To compare gephyrin cluster dynamics on short and longer time scales in different conditions, two apparent diffusion coefficients D ini and D 20 -30 were derived by fitting the MSD curve with the linear function MSD(t) ϭ 4 D a-b ϫ t ϩ C a-b , between a ϭ 1 and b ϭ 4, a ϭ 20 and b ϭ 30, respectively.…”
Section: Introductionmentioning
confidence: 99%